A modern approach to practice of banking in Nigeria : lending principles & securities - Udendeh, Gabriel (Kaduna, Nigeria : M.O. Press & Publishers Ltd, 2015)
This book is carefully researched work predicated on practice and basic laws of banking that have evolved over time.
Includes bibliographical references and index.
aia 25/10/17
Loans
Keywords: Banks and banking; Lending principles; Nigeria